Determination of Women's Skincare Product Purchase Decisions: The Role of Halal Labels, Lifestyle, and Brand Awareness - Firmansyah, Farhandika Rahid; Humairoh, Humairoh (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to determine the role of halal labels, lifestyle, and brand awareness on women's skincare product purchasing decisions in Tangerang City. The object of the study focused on consumer behavior, where skincare products were used as the context, with Wardah being the most frequently chosen brand by respondents. This study used a quantitative approach with a purposive sampling technique. The sample size was 100 respondents with an age range of 15 to 54 years. Data collection was carried out through a questionnaire with a Likert scale. Data analysis using SPSS version 25 included descriptive statistical analysis, validity and reliability tests, classical assumption tests, regression tests, correlation tests, coefficient of determination tests, and hypothesis tests. The results showed that partially halal labels, lifestyle, and brand awareness had a positive and significant effect on purchasing decisions. Simultaneously, these three variables also had a positive and significant effect on purchasing decisions. The coefficient of determination value of 0.597 indicated that halal labels, lifestyle, and brand awareness were able to explain purchasing decisions by 59.7%, and the remaining 40.3% was influenced by other factors outside this study. This study shows that clarity of halal labels, lifestyle compatibility, and brand awareness play a significant role in driving skincare product purchasing decisions. Limitations of this study lie in the combination of variables used and the focus on female skincare consumers in Tangerang City. The results are expected to inform business owners' considerations in developing more effective marketing strategies.